Interactive roles of resource availability, role clarity and employee motivation in enhancing organisational effectiveness through employee performance and job satisfaction - Lebbaeus Asamani; Richmond Acquah-Coleman; William Kwesi Senayah; Seth Oppong (Discover Psychology)
Abstract The current study explores the interplay between resource availability, role clarity, and employee motivation in predicting organisational effectiveness through employee performance and job satisfaction within the garment industry. We collected data from 306 employees in a cross-sectional survey and analyzed it using partial least squares structural equation modelling. Resource availability significantly predicted job satisfaction, while role clarity and employee motivation, together with job satisfaction, positively predicted employee job performance. Finally, resource availability, employee motivation, and job satisfaction positively predicted organisational effectiveness. Given the unique labour-intensive nature of the garment industry, this study extends the existing literature and provides practical implications for enhancing organisational effectiveness within this unique context. Essentially, the findings offer valuable insights for industry stakeholders on optimising resource utilisation, enhancing job satisfaction, and fostering employee motivation to achieve better organisational outcomes.